Legal Protection and the Implementation of Rights of Pregnant Women in Detention: A Case Study of the Class IIA Women’s Correctional Facility in Medan, Indonesia - Sophia Harahap; Rasina Padeni Nasution (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study investigates the legal protection and implementation of rights for pregnant women in detention at the Class IIA Women’s Correctional Facility in Medan, Indonesia. Although Indonesian correctional law and human rights instruments provide normative guarantees, their realization is constrained by structural and institutional challenges. Using an empirical juridical approach and qualitative case study design, data were collected through semi-structured interviews with key prison staff, direct observation, and analysis of relevant legal and policy documents, including the Directorate General of Corrections’ Basic Health Service Standards. Findings indicate that while basic healthcare, medical referrals, nutritional support, and partial psychosocial services are available, their effectiveness is limited by the absence of obstetric specialists, lack of dedicated housing for pregnant detainees, budget constraints, and insufficient continuous psychosocial support. This highlights a gap between formal legal guarantees and substantive protection, demonstrating that formal equality alone cannot address the differentiated needs of pregnant detainees. Policy recommendations include measurable operational standards, intersectoral integration with local healthcare services, gender- and human rights-based staff training, and performance-oriented evaluation. The study contributes to socio-legal scholarship by emphasizing that effective protection of vulnerable groups depends on both normative frameworks and institutional capacity oriented toward human-centered justice.